Pemikiran Moderen Islam: Geneologi Dan Peran Muhammad Abduh Dan Rifaah Al-Tahtawi - Aulia Rahman (Tasamuh: Jurnal Studi Islam, 2024)
Historically, modern thought in Islam was introduced by Muhammad Abduh and Rifaah al-Tahtawi. This article wants to describe the geneology of thought and the role of Muhammad Abduh and Rifaah al-Tahtawi who influenced modern thought in Islam. The research method is qualitative research that refers to the historical paradigm with its source on the role of Muhammad Abduh and Rifaah al-Tahtawi in descriptive form. The data were obtained from journals and other sources related to Muhammad Abduh and Rifaah al-Tahtawi. The result of this research is Islamic modernism is an adaptation of Islam or interpretation of Islam adapted to the context of modern times. The aim of renewal in the Islamic world is the encouragement to examine and re-explain Islamic doctrines in a language and formulation acceptable to modern minds. Tahtawi had a role in introducing Francis' civilization especially to Egyptian readers. He translated many books on legal thought, philosophy, engineering, physics from Francis into Arabic. While Abduh's role was to develop a more specific idea, namely reformism and develop theological thinking that was rational. The geneology of modern thought in Islam is illustrated in the efforts to continue the spirit of al-Tahtawi by al-Afghani, Muhammad Abduh and Rashid Ridha.